Numerical Analysis of Two Term Model Using Newton’S Method on Drying Kinetics of an Improved Cowpea (It 97K-56S-Is) - Ajao, T. O.; Raji, A. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
Invention of computers has made numerical methods prevalent and widely accepted. Different numerical methods exist but all aid in solving large numbers of tedious arithmetic calculations involving complex differential equations and so an analytical solution cannot be applicable, hence, computer simulations and numerical solution become functional. IT 97K-56S-IS, a high yielding, multiple disease resistant cowpea variety with maturity date of 60Days was gotten from the International Institute of Tropical Agriculture (IITA). Experiments were carried out on samples after harvesting at maturity in a convective dryer at drying temperature of 55, 65, 75 and 85ºC and drying kinetics was performed utilising the Two term model. The model was numerically solved using Newton Raphson’s iterative method on account that it is a non linear equation, its fast convergence to the roots and requirement of a single guess. A well structured algorithm was written. The performance of the models was evaluated using the coefficient of determination (R^2) and root mean square error (RMSE) showing the relationship between the experimental and predicted moisture ratios. The result shows that Newton Raphson’s method would be suitable for Two-Term model if used with a multiplication factor or constant.